LEGAL CERTAINTY TERM OF PROTECTION TRADEMARKS FOR SME AND IKM ACTORS - Muldri Pudamo James Pasaribu; Rony Andre Christian Naldo; Anggiat Sinurat (Faculty of Law, Universitas Pekalongan, 2023)
The practice of SMEs and IKM which are the most developed business units in Indonesia. Regarding its development, in order to create legal certainty and obtain legal protection, every SME and IKM actor should register their trademark. For applications for registration of trademarks that are accepted, SMEs and IKM actors obtain rights to trademarks, which furthermore the Menkumham via DGIP issues trademark certificates, the official excerpt of which can be obtained by SMEs and IKM actors through filing an application by paying an official fee. This study discusses the registration of trademarks by SME and IKM business actors and/or their proxies in order to create legal certainty and obtain legal protection. In this regard, this study uses the Theory of Legal Certainty, focused on examining legal certainty regarding the term of trademark protection for SMEs and IKM actors. This research is a type of normative research. The method used in this study is a normative juridical research method. This research is a prescriptive analysis, using various types of data in legal research related to national and regional economic growth. The results of the study conclude that legal certainty for trademark legal protection for SMEs and IKM actors is 10 (ten) years from the date of receipt, and can be extended for 10 (ten) years. In Law Number 20 of 2016, there is no legal certainty regarding the application for further extension by SMEs and IKM actors who own trademarks and/or their proxies in order to obtain trademark legal protection. Tariffs related to the registration or extension of trademarks have been determined by the Government in Government Regulation Number 28 of 2019.